Hybrid Nanoparticles Dual-Loaded With Curcumin and Benzydamine Hydrochloride for the Treatment of Vulvovaginal Candidiasis: From Development to Biological Application In Vitro and In Vivo - Carvalho, Gabriela C. [UNESP]; Domingues, Maria Nolasco Viseu; Marena, Gabriel Davi [UNESP]; Mäkilä, Ermei; Li, Jiachen; Geertsema-Doornbusch, Gésinda; de Andrade, Cleverton Roberto [UNESP]; Stuart, Marc C. A.; Shahbazi, Mohammad-Ali; Corrêa, Ione [UNESP]; Peterson, Brandon W.; Salonen, Jarno; et al. (Wiley, 2025)
Vulvovaginal candidiasis represents a public health challenge due to its reports of high incidence and recurrence. These are caused by host-related factors like compromised immune system, or pathogen-related factors, such as resistance to antifungal agents, making this medical problem desirable to develop new therapeutic options. In this context, natural origin substances like curcumin, are increasingly treatment alternatives. However, some curcumin properties limit its therapeutic application, such as insolubility in aqueous solvents, which leads to low bioavailability. Nevertheless, nanotechnology association with drugs of plant origin proves to be a promising alternative to overcome the reported drawbacks. Despite being caused by a fungus, patients suffer significantly from the inflammation resulting from this disease, thus this study aimed to develop a hybrid carrier nanoformulation by microfluidics loaded with two drugs, benzydamine hydrochloride (an anti-inflammatory drug) and curcumin (an antifungal drug). Transmission electron cryomicroscopy combined with energy dispersive X-ray analysis confirmed that the nanoparticle is properly developed. Through in vitro biological studies, it is possible to observe that, in addition to being safe, the encapsulation of both drugs in the nanocarrier drastically reduced their cytotoxicity. Finally, although the final nanoformulation does not show in vitro activity, the in vivo study indicated therapeutic potential.
Keywords: benzydamine hydrochloride; curcumin; lipids; mesoporous silica nanoparticles; thermo-responsive hydrogel; vulvovaginal candidiasis